THE EFFECT OF CAPITAL, LIQUIDITY AND CONSUMER PRICE CHANGES ON FINANCING RISK - Hardiansyah Padli; Rahma Detik Kurningsih (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing Deposit to Ratio (FDR) and inflation on Non-Performing Finance (NPF) in the short and long term. By using time series data for the monthly period from 2015-2019 and the Error-Correction Model (ECM) and cointegration approach, it is found that CAR does not have a significant effect on NPF in the short and long term. FDR in the short term does not have a significant effect on NPF, in the long term FDR has a significant effect on NPF. Meanwhile, inflation has a significant effect on NPF both in the short and long term.